MANAGEMENT OF A RARE CASE OF PEDIATRIC DEEP STERNAL WOUND INFECTION WITH VACUUM-ASSISTED CLOSURE (VAC) - Ramli, Rianto Noviady; Kusumaputri, Ayu Prima; Prabowo, Arif Yudho; Kurnia, Yunanto; Prawoto, Almas Nur (Universitas Airlangga, 2022)
HIGHLIGHTS: 1.This case series demonstrates that the combination of micro and nano fat shows promising results for overcoming facial contour deformity.2. Growth factors and stem cells in nano fat complemented the micro fat properties, thus increasing the survivability rate. ABSTRACT: Background: Patients with craniofacial clefts who have had reconstructive surgery often develop problems,such as contour deformity that will cause psychological issues. Micro and nano fat grafting are various methods utilized to overcome these issues. Case and Operation Technique: This case series describes two patients with facial contour deformities due to Tessier 3 and 4 craniofacial clefts, respectively. Each patient underwent secondary reconstruction correction surgery followed by a combination of micro and nano fat grafting. Discussion: Results on day 7 after surgery were promising. Growth factors and stem cells in nano fat complemented the micro fat properties, thus increasing the survivability rate. Conclusion: This case series demonstrates that the combination of micro and nano fat shows promising results for overcoming facial contour deformity.